1991
DOI: 10.1146/annurev.so.17.080191.002443
|View full text |Cite
|
Sign up to set email alerts
|

Sport and Society

Abstract: Sport is a very prominent social institution in almost every society because it combines the characteristics found in any institution with a unique appeal only duplicated by, perhaps, religion. The functional, conflict, and cultural studies perspectives are reviewed, with additional discussion on how sport relates to the processes of socialization and social change. The latter focusses on the evolution of sport from a playful, participation-oriented activity to one that resembles a corporate form guided by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
2

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(60 citation statements)
references
References 37 publications
0
57
0
2
Order By: Relevance
“…For example, white athletes traditionally dominate the positions of pitcher and catcher in baseball; quarterback, center, and middle linebacker in football; and (traditionally) the point guard in basketball. Black athletes have been found to disproportionately occupy the positions of running back, receiver, and defensive line in football, outfield positions in baseball, and (traditionally) the forward position in basketball (Coakley 2007;Knee 2003;Spence 2000;Lomax 1999;Jibou 1988;Frey and Eitzen 1991;Medoff 1976). The "skill" positions were believed to require greater intelligence, decision-making abilities, and leadership, while the non-central positions were thought to require dominant physical skills: speed, strength, and agility.…”
Section: Race In Sportsmentioning
confidence: 99%
“…For example, white athletes traditionally dominate the positions of pitcher and catcher in baseball; quarterback, center, and middle linebacker in football; and (traditionally) the point guard in basketball. Black athletes have been found to disproportionately occupy the positions of running back, receiver, and defensive line in football, outfield positions in baseball, and (traditionally) the forward position in basketball (Coakley 2007;Knee 2003;Spence 2000;Lomax 1999;Jibou 1988;Frey and Eitzen 1991;Medoff 1976). The "skill" positions were believed to require greater intelligence, decision-making abilities, and leadership, while the non-central positions were thought to require dominant physical skills: speed, strength, and agility.…”
Section: Race In Sportsmentioning
confidence: 99%
“…The media often plays an integral role in amplifying issues into social problems (Tuchman 1978;Johnson 1989;Lynch et al 1989;Frey and Eitzen 1991 ). This certainly has been true of the drug scare of the 1980s (e.g., Reinarman and Levine 1989) and past antidrug campaigns (e.g., Becker 1963;Gusfield 1963;Musto 1973;Levine 1984;Himmelstein 1983).…”
Section: Newspaper Reporting and Additional Agendasmentioning
confidence: 99%
“…Studies have shown that white athletes have historically been overrepresented and black athletes underrepresented, in "key functionary" roles: positions that have a greater impact on the outcome of games and which require intelligence, decision-making ability, and leadership. In football the key functionary positions are generally quarterback, center, and middle linebacker (see Coakley 2007;Ogden and Hilt 2003;Lomax 1999;Frey and Eitzen 1991;Jibou 1988).…”
Section: Discussionmentioning
confidence: 99%